Left ventricular dyssynchrony assessment using tissue synchronization imaging in acute myocardial infarction - Ahmed S Azazy (Thieme Medical and Scientific Publishers Pvt. Ltd., 2019)
Objectives: To assess left ventricular (LV) dyssynchrony in patients with ST elevation myocardial infarction (STEMI). Background: Mechanical synchronization disorder leads to a decrease in LV ejection fraction (LVEF) and stroke volume, an abnormal distribution of wall tension, and increase in workload during cardiac contraction. Methods: We enrolled 56 participants, 36 with acute STEMI and 20 healthy controls. The automatically color-coded time to peak myocardial velocity was measured using a 6mm sample volume, manually positioned within the two-dimensional-tissue strain image of the 12 basal and middle LV segments. Results: A significant delay was found between the septal-lateral and septal-posterior walls in patients with STEMI compared to patients in the control group (36.36 vs. −6.0ms, P = 0.036; and 42.7 vs. 23.94ms, P = 0.042, respectively). Furthermore, all segment maximum differences and all segment standard deviation (SD; dyssynchrony index) were found to be significantly higher in the STEMI group (131.28 vs. 95.45ms, P = 0.013; and 44.47 vs. 26.45ms, P = 0.001, respectively). A significant delay between the septal-lateral walls and septal-posterior walls, all segment maximum difference, and all segment SD (dyssynchrony index) were found in patients with complicated STEMI (70.89 vs. 15.83ms, P = 0.038; 57.44 vs. 19.06ms, P = 0.040; 138.11 vs. 100.0ms, P = 0.035; and 45.44 vs. 32.50ms, P = 0.021, respectively). There was a significant negative correlation between tissue synchronization imaging parameters and LVEF, and a positive correlation with LV end systolic dimension. Conclusion: Patients with acute STEMI showed significant LV dyssynchrony, which was an independent predictor of inhospital complications.